International Students’ Experience of Studying and Working at a Northeastern Public University in the US - Kwadzo, Moses (Journal of International Students, 2014)
This study explores international students’ experiences with studying and working at a North Eastern public university. Through phenomenological research approach that utilized face-to-face interview and photo-elicitation techniques, the personal experiences of twenty international students were captured. The findings of this study indicated that these students benefited from the responsibilities that resulted from their dual role as both students and employees in many ways. However, they also suffered from emotional and physical stress which resulted in tiredness, lack of sleep, role conflict, homesickness and frustration. Interestingly, these students effectively employed different coping mechanisms including finding social support, and participating in leisure and nonleisure activities to off-set the negative effects of studying and working concurrently.